Case Report: Chediak Higashi Syndrome with Hemophagocytic Lymphohistiocytosis - Mazhar, Nimra; Minhas, Aiman Mahmood; Nasir, Asma; Insari, Rabia; Imran, Ayisha (International Journal of Pathology, 2024)
Chediak higashi syndrome (CHS) is a rare autosomal recessive disorder characterized by albinism, recurrent chest infections and neurological dysfunction. Although a rare disorder but is commonly encountered. Diagnosis of CHS is challenging and most infants remain undiagnosed leading to poor life quality. In this case report, we discuss a 3 years old child that presented to Chughtai institute of Pathology, Lahore. Patient was transfusion dependent and other than fair skin and greyish hair, he also had splenomegaly. His bone marrow biopsy was performed and findings were consistent with CHD with secondary HLH.